Islands in the Rainforest : Landscape Management in Pre-Columbian Amazonia - Rostain, Stéphen (New frontiers in historical ecology, 2013)
Stéphen Rostain's book is a culmination of 25 years of research on the extensive human modification of the wetlands environment of Guiana and how it reshapes our thinking of ancient settlement in lowland South America and other tropical zones. Rostain demonstrates that populations were capable of developing intensive raised-field agriculture, which supported significant human density, and construct causeways, habitation mounds, canals, and reservoirs to meet their needs. The work is comparative in every sense, drawing on ethnology, ethnohistory, ecology, and geography; contrasting island.